Current and future antiviral drug therapies of hepatitis B chronic infection - Koumbi, Lemonica (World J Hepatol, 2015)
Despite significant improvement in the management of chronic hepatitis B virus (HBV) it remains a public health problem, affecting more than 350 million people worldwide. The natural course of the infection is dynamic and involves a complex interplay between the virus and the host’s immune system. Currently the approved therapeutic regimens include pegylated-interferon (IFN)-α and monotherapy with five nucleos(t)ide analogues (NAs). Both antiviral treatments are not capable to eliminate the virus and do not establish long-term control of infection after treatment withdrawal. IFN therapy is of finite duration and associates with low response rates, liver decompensating and numerous side effects. NAs are well-tolerated therapies but have a high risk of drug resistance development that limits their prolonged use. The imperative for the development of new approaches for the treatment of chronic HBV infection is a challenging issue that cannot be over-sided. Research efforts are focusing on the identification and evaluation of various viral replication inhibitors that target viral replication and a number of immunomodulators that aim to restore the HBV specific immune hyporesponsiveness without inducing liver damage. This review brings together our current knowledge on the available treatment and discusses potential therapeutic approaches in the battle against chronic HBV infection.